Amphiphilic and Zwitterionic Multi Arylpyrroles with Near‐Infrared Aggregation‐Induced Emission for Cell Membrane Imaging. Issue 7 (1st June 2022) - Li, Ziting; Cui, Shisheng; Yu, Jiayu; Qu, Jiamin; Shi, Jianbing; Tong, Bin; Cai, Zhengxu; Dong, Yuping
Abstract: The cell membrane protects the cell stability and balance and participates in various physiological activities as an exchange channel. Therefore, the real‐time monitoring of cell membrane biological dynamics can help us understand the physiological state of the current cell. Herein, a type of amphiphilic near infrared (NIR) aggregation‐induced emission (AIE) molecules was designed and synthesized. Multiarylpyrroles (MAPs) with a dodecyl chain at the 1‐position of the pyrrole ring, charged pyridinium sulfonate at the 2, 5‐position of the pyrrole ring and free rotating aryls at the 3‐position of the pyrrole ring can target cell membranes. One of the MAPs, MAP22, had a maximum emission wavelength in the aggregation state of up to 721 nm with a large Stokes shift (∼280 nm). In addition, MAP22 nanoparticles can produce reactive oxygen species (ROS) with a quantum yield of 224%. Therefore, these AIE MAPs are promising candidates for theranostic nanoagents, including NIR fluorescence imaging to target cell membranes and ablate cancer cells by producing ROS. Abstract : A near infrared (NIR) amphiphilic multiarylpyrroles MAP22 with aggregation‐induced emission (AIE) property was synthesized for cell membrane imaging, mainly due to the long alkyl chain and electrostatic interaction. MAP22 also had the ability to produce reactive oxygen species (ROS) under light irradiation.